ANALYSIS OF THE EMOTIONAL USER EXPERIENCE ON NETFLIX INDONESIA'S EMOTIONAL BRANDING THROUGH INSTAGRAM ACCOUNTS - Agatha, Sheilla Claudy; Swarnawati, Aminah (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
The rise of Over the Top (OTT) internet content services like Netflix has revolutionized the entertainment industry. Netflix Indonesia employs emotional branding through the Instagram account @netflixid. The research aims to describe user experiences with Netflix Indonesia's emotional branding on Instagram and analyze it through the @netflixid account based on user experiences. Using marketing communication theory, specifically emotional branding, the qualitative descriptive research with a phenomenological approach involved four purposively selected informants. Results reveal an emotional bond between users and the Netflix brand through the @netflixid Instagram account. This emotional experience involves feelings, emotions, and psychological reactions during interactions with content uploaded by Netflix Indonesia on its account, @netflixid. Netflix's Instagram content, encompassing relationship elements, sensory experiences, imagination, and vision, is crucial in emotional branding. Additionally, the study discovered that posts featuring behind-the-scenes content, user-generated content, and interactive polls further strengthened the emotional connection between users and Netflix. This research highlights the connection between user emotional experiences and Netflix Indonesia's emotional branding through the @netflixid Instagram account. The study underscores the importance of leveraging social media platforms to enhance brand loyalty and user engagement. Moreover, it suggests that continuous engagement and timely responses to user comments on Instagram posts significantly contribute to the emotional bond between the brand and its audience. By understanding and implementing these strategies, Netflix Indonesia can further solidify its position in the competitive OTT market, ensuring long-term success and sustained user satisfaction